PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN LABIRIN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 122399 PEMATANGSIANTAR - Emmy Sartika Manullang; Yanti A Sidabutar; Muktar B Panjaitan (STKIP Subang, 2025)
The Effect of Using Maze Learning Media on Mathematics Learning Outcomes of Second Grade Students at SDN 122399 Pematangsiantar This study aims to determine the effect of Maze Learning Media on Mathematics Learning Outcomes of Second-Grade Students at SDN 122399 Pematangsiantar. This study used quantitative research using a pre-experimental method. Based on the results, student learning outcomes were obtained with an average pretest score of 53.73, and after treatment using Maze Media, an average score of 85.76 was obtained. The t-test results showed that t = 9.946 > t = 2.069. If t > t then Ho is rejected and Ha is accepted. It is concluded that the Maze Media has been effectively implemented.